Total Polyphenol content in five nuts - Jelena, Rajić; Stanković, Sofija; Bašić, Jasmina; Govedarica, Ilija (Archives of Pharmacy, 2022)
Experimental data increasingly support the hypothesis of a preventive effect of a diet rich in fruits and vegetables. It has long been thought that this effect should be attributed to the antioxidant effects of vitamins. Attention is increasingly paid to compounds that are not vitamins, and especially polyphenols.Nuts contain a large amount of unsaturated fatty acids, and are relatively stable, so we can conclude about the high content of antioxidant compounds. Earlier, it was considered that this activity mostly belongs to tocopherol, but new, extensive research has also pointed out the importance of polyphenols. Walnut, as the most commonly used nut, has been the most studied and more than 20 different polyphenols have been found, although it is believed that there are many more. The aim  of this work was to evaluate total polyphenol content in several nuts. For this study, five types of nuts were selected from three different producers: peanuts, Brazil nuts, hazelnuts, almonds and walnuts. The content of total phenolic compounds was determined  using  spectrophotometric Folin – Ciocalteau method. Total polyphenol content in different types of nuts varied greatly both between the types and within the same type depending on the producer. The highest was in walnut 2228.68 ± 355.70 mgGAE/ 100g while the lowest value was obtained in almonds 102.40 ± 20.44 mgGAE/100g.